Multiple Voices to the Development of a Critical and Responsible Citizenship - Ana Paula Caetano; Isabel Freire (Universidade de Lisboa, 2014)
This paper presents reflections on education and citizenship and the issues addressed, arising from three research projects with distinct methodologies. These projects have transversely advocated human dignity and the value of participation, interdependency, and responsibility among human beings, particularly those involved in more vulnerable situations. In the project Cyberbullying - a diagnostic of the situation in Portugal, the importance of understanding violence phenomena by identifying risk and protection factors has been evidenced, highlighting the relevance of an education based on co-responsibility, and an ethic of care. In the critical ethnographic project Urban Boundaries - the dynamics of cultural encounters, discussions evolved around communitarian education, and education was understood as a movement aggregating several dimensions of the project and including members of the local communities actively advocating their rights. In the project Voices of youth in the development of intercultural education, the value of children and youngsters' participation in social transformation was highlighted, streamlining initiatives with the school community through dialogic, artistic, and technologic processes that promoted the development of intercultural competences.